1998
DOI: 10.1046/j.1365-2869.1998.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Evening administration of melatonin and bright light: Interactions on the EEG during sleep and wakefulness

Abstract: SUMMARY Both the pineal hormone melatonin and light exposure are considered to play a major role in the circadian regulation of sleep. In a placebo-controlled balanced cross-over design, we investigated the acute effects of exogenous melatonin (5 mg p.o. at 20.40 hours) with or without a 3-h bright light exposure (5000 lux from 21.00 hours-24.00 hours) on subjective sleepiness, internal sleep structure and EEG power density during sleep and wakefulness in healthy young men. The acute effects of melatonin, brig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 3 publications
3
66
2
Order By: Relevance
“…10 Furthermore, acute suppression of the night time melatonin surge -either by light or beta-blockers -compromises sleep quality, which can be reversed by melatonin supplementation. 5,6 However, whether the chronic absence of night time melatonin secretion leads to compromised sleep is unclear. The results of the present study suggest that the absence of night time melatonin secretion results in chronically reduced sleep quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Furthermore, acute suppression of the night time melatonin surge -either by light or beta-blockers -compromises sleep quality, which can be reversed by melatonin supplementation. 5,6 However, whether the chronic absence of night time melatonin secretion leads to compromised sleep is unclear. The results of the present study suggest that the absence of night time melatonin secretion results in chronically reduced sleep quality.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates that the neural pathway for the endogenous production of melatonin passes through the cervical spinal cord. 4 Since exogenous melatonin can shorten sleep onset, improve sleep maintenance, and increase REM sleep, [5][6][7] we hypothesized that the absence of endogenous night time melatonin in subjects with cervical SCI would lead to prolonged sleep onset latency, reduced sleep efficiency, and reduced REM sleep.…”
Section: Introductionmentioning
confidence: 99%
“…When used near the time of habitual sleep, melatonin has produced less consistent results. Nocturnal administration has been reported to promote sleep (23,24), to have no significant clinical benefit (25) or to even increase wake time after sleep onset (26). Such variability may be related to differences in inclusion and exclusion criteria, outcome measures, hormone dose, and routes and timing of its administration.…”
Section: Discussionmentioning
confidence: 99%
“…It elicits time-dependent soporific effects, which have been corroborated with electrophysiological mea sures of sleepiness such as (EEG) theta activity during wakefulness (Cajochen et al, 1997b) and with brain correlates of sleepiness in an fMRI study, which highlighted the role of melatonin in priming sleep-associated brain activation patterns in anticipation of sleep (Gorfine et al, 2006). In an experiment where we blocked the natural evening increase in heat loss, subjective sleepiness, and melatonin secretion by light exposure, we could show that melatonin replace ment (5 mg) acutely recovered the evening increase in heat loss, subjective sleepiness, and also theta activity in the waking EEG (Cajochen et al, 1998;Krä uchi et al, 1997). Nighttime melatonin administration does not affect sleep consolidation or sleep efficiency (Cajochen et al, 1997a), whereas, during day time, an improvement in sleep efficiency could be found .…”
Section: B Effects Of Exogenous Melatonin On Human Sleep and Wakefulmentioning
confidence: 91%
“…However, several lines of evidence suggest that endogenous melatonin levels may still play a role in consolidated sleep and/or wakefulness. Acute suppression of the nighttime melatonin surge-either by light or beta-blockers -compromises sleep quality, which can be reversed by melatonin supplementation (Cajochen et al, 1998;Van Den Heuvel et al, 1997). In a survey of 13 adult pineal surgery patients, over half the patients (54%) reported nighttime wake periods lasting 1 h or longer, 31% reported total nighttime sleep durations of less than 6 h, and 38% complained of experiencing poor or disturbed sleep every night (Macchi et al, 2002).…”
Section: A Endogenous Melatonin and The Human Circadian Sleep-wake Cmentioning
confidence: 99%